The Effect of Using Educational Multimedia in Dictation on Students’ Listening Comprehension at MA Darul Hikmah Pekanbaru - Rahmat, Agustina Yusuf (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
The main goal of the study was to investigate the effect of using educational multimedia in dictation on students’ listening comprehension at MA Darul Hikmah Pekanbaru. This was a quasi-experimental research which involved control class and experimental class. The population of the study was 175 and the sample was 52. The instrument of the study had been tested its validity and reliability by conducting try-out test two times. The instrument was given in control class and experimental class before and after giving treatments. The treatments were only given to experimental class meanwhile in control class remained using the conventional teaching technique. The data were analyzed by using indipendent sample t-test and paired sample t-test then the effect size and improvement were calculted. The result of the study shows that both control class and experimental class had improvement of their listening comprehension. But, the improvement of experimental class was much higher that control class was. The improvement of listening comprehension in experimental class was  43,2% but in control class was only 11,5%. In short, it can be concluded that the using of educational multimedia in dictation provely could improve students’ listening comprehension.